Malignant giant cell tumor of the uterus: a case report - Oliveira, Rivadávio Antunes Menacho de; Stecca, Carlos Eduardo; Silva, Tassiara; Piovesana, Mariana Miyasaki; Peron, Veruska; Gordan, Angela (Brazilian Journal of Oncology, 2021)
This report describes a rare case of malignant extraosseous giant cell tumor (GCT). It refers to a patient with an initial diagnosis of a locally advanced malignant GCT of the uterus, with disease progression to lung and mediastinum seven months after the diagnosis, requiring first line treatment with chemotherapy. Extraosseous presentation of GCT with early distant dissemination is unusual and the role of systemic cytotoxic treatment remains unclear.
Keywords: Giant cell tumor; Uterine; Uterus.